How Does Realistic Mathematics Education (RME) Improve the Numeracy Skills of Students in Elementary School? - Irfan Fauzi; Jiraporn Chano; Andika Arisetyawan (CV. Creative Tugu Pena, 2025)
This research aims to determine the impact of realistic mathematics education on the numeracy skills of elementary school students. The population of this study is fourth-grade students in elementary schools in Bandung. The sample in this study consists of 82 students from fourth grade at one of the elementary schools in Bandung. This research uses a positivist paradigm with a quantitative approach. The method used is a pre-experiment. The instrument is a numeracy test comprising 35 questions (multiple choice, complex multiple choice, matching, fill in the blank, and essay). The test material includes geometry and statistics. Data analysis using Microsoft Excel to calculate descriptive statistics and SPSS type 24 to calculate inferential statistics. The results show that the significance of the Wilcoxon test is 0.000. This means there is a difference in the pre-test and post-test scores of numeracy skills of 4th-grade elementary school students. The average pre-test score is 47, and the post-test score is 69. After implementing the Realistic Mathematics Education (RME) approach, students' numeracy skills increased by 22 points. Based on the N-Gain score of 0.42, this improvement in students' numeracy skills is categorized as medium. This study implies the importance of Realistic Mathematics Education in mathematics learning and recommends its consistent application and the development of relevant teaching materials for elementary school students.